Evaluation of models for estimating the reference evapotranspiration in colombian coffee zone (2011)
The reference evapotranspiration (ETo) is an important variable for hydrological studies, crop water requirements estimations, climatic zonification and water resources management. The FAO recommends the Penman-Monteith (P-M) and/or the Hargreaves models as the worldwide useful for the ETo calculation.The objective of this work was to test the performance of these models in one place of the Colombian Coffee Belt, and identify limitations and proposes modifications. The ETo calculation were compared with daily lysimeter measurements. The principal disadvantages of the P-M model were: the lack of calibrated coefficient for the long wave radiation estimation (Rnl) which affected seriously the net radiation estimation and finally the ETo, highly sensitivity at the wind speed changes, that make it inappropriate for locations without this data. The Hargreaves model, as FAO proposed, overestimate the ETo, which made necessary a modification. The ETo estimation for this location was most sensible to atmospheric vapour and air temperature than the available energy in the atmosphere (Rn-G).